Isotopic and Elemental Determination in Some Romanian Apple Fruit Juices - Dana Alina Magdas; Adriana Dehelean; Romulus Puscas (The Scientific World Journal)
H, C, O stable isotope ratios and the content of some heavy elements of 31 Romanian single-strength organic apple juices collected from four Transylvanian areas are discussed in this study. The aim of this study was to measure the 2H/1H, 18O/16O, 13C/12C ratios of these juices and their elemental profile and to establish a database of authentic values to be used for adulteration and authenticity testing. Our results have shown mean values of δ18O=-4.2‰ and δDδ-46.5‰, respectively, for apples from Transylvania and at the same time the mean value of δ13C=-28.2‰. The content of Cd, Pb, U, Zn, As was below the acceptable limits stipulated in US-EPA standard for drinking water. Cu and Cr limits exceeded for one single juice; Ni content for some apple juices from Maramures, Alba, and Cluj was higher than the acceptable value.